MIĘDZY KONIECZNOŚCIĄ A MOŻLIWOŚCIAMI – PRZEKSZTAŁCENIA W RESORCIE SPRAW WEWNĘTRZNYCH W OKRESIE TRANSFORMACJI USTROJOWEJ W POLSCE; ASPEKTY ORGANIZACYJNO-PRAWNE - Majer, Piotr (Zeszyty Prawnicze, 2016)
BETWEEN THE NECESSITY AND CAPABILITIES – TRANSFORMATIONS IN THE INTERNAL AFFAIRS DEPARTMENT DURING THE POLITICAL TRANSFORMATION; THE ORGANIZATIONAL AND LEGISLATIVE ASPECTS Summary The reconstruction of the Ministry of Internal Affairs was a very important task in the process of political transformations initiated in Poland in 1989. This postulate, made under the provisions of the statutory law, was materialised in 3 resolutions adopted by the Parliament on 6 April 1990. Pursuant to the provisions of those resolutions , the internal affairs minister was deprived of his law enforcement powers, becoming solely the supreme body of state administration implementing national policies in the area of state protection, security and public order. The above functions were transferred to the respective agencies reporting to the minister. In the successive resolutions adopted on 6 April 1990, the Parliament set forth the powers and organisational principles of two such agencies – the Police and the State Protection Office. The above began operations on 10 May 1990 when the said resolutions came into force. In the final part of the article, the author discusses the controversy surrounding the drafting of the above resolutions, including staff affairs relating to the winding up of the Security Service and the Citizens’ Militia.